Structure and quality assurance of Fellowship Training in General Surgery: Consensus recommendations from the Association of Surgeons in Training. (July 2019) - ,; ,; ,; ,; Fleming, Christina; Pucher, Philip; Elsey, Elizabeth; Glasbey, James; Conneely, John; Hogan, Aisling; Adair, Robert; Lund, Jonathan; et al.
Abstract: Background: Over three-quarters of surgical trainees intend to undertake clinical fellowships to improve competence, confidence and the development of super specialised skills. At present there is no standardised national regulation for fellowships in the UK, leading to variability. The Association of Surgeons in Training (ASiT), an organisation representing surgical trainees in the UK and Ireland, sought to provide recommendations on the structure and quality assurance of fellowships in General Surgery. Methods: A consensus session was held by ASiT at the Association of Surgeons of Great Britain and Ireland (ASGBI) 2017 Congress in Glasgow. A variety of perspectives on fellowships were presented by invited speakers, and thereafter a moderated discussion ensued in order to reach consensus. Live-polling using an electronic application facilitated consensus discussions. A writing group thereafter developed an initial consensus document which was then subject to electronic review by all authors and by ASiT council. Results: Thirty-four delegates attended the consensus session. Views of the delegates and online discussants were that fellowships should be optional and not mandatory. There was (n = 16) no preference expressed between UK and international fellowships by half the group, while half expressed a preference for international fellowships. Regarding UK fellowships, the majority (n = 24) said that national registration of such fellowships should be established and (n = 23) agreed that a defined curriculum was required. However, national selection into fellowship training was not supported (n = 20). Perceived advantages of UK fellowships included ease of relocating within the same country (which was considered more family-friendly and cost-effective), and familiarity with the NHS system. Delegates considered the advantages of international fellowships to include: access to high-volume centres; diversity of case-mix; and structured, regulated fellowship programmes. Conclusion: The consensus session found unanimous support for maintaining the option of both UK and international fellowships. While trainees support quality assurance of fellowships, they do not support a national selection process.